KEBANGKITAN LOKAL DI ACEH: PEMBENTUKAN IDENTITAS KEACEHAN, REAKTUALISASI RUANG PUBLIK DAN PENGUATAN KEARIFAN LOKAL PASCA KONFLIK DAN TSUNAMI - Ibnu Mujib; Irwan Abdullah; Heru Nugroho (Harmoni, 2014)
This paper explores the new form of Acehnese identity that has inspired the revival of the local in Aceh. Two important points will be explored in this paper: 1) the idea of a new Aceh and 2) how this Aceh revivalism is formulated from within. This paper studies the process of dialogue and renegotiation of local wisdom and practices and Acehnese identity in public space. This study shows that the renegotiation of public spaces that were essentially demolished due to the former conflict and the tsunami is now being rebuilt to revive the social bases that had been lost. The discourse of local wisdom has been implemented through the Qonun to maintain and implement Aceh’s intellectual heritage. This communal consciousness has been actively built by many actors through various forms of dialogue and negotiation. It is thus not surprising to see an upsurge in meunasahs, gampong activities, the revival of the mosque as the center of Islamic studies, and even the centering of coffee shops in Acehnese identity. These activities are all part of the idea of Aceh revival.